Optimal control with backstepping method for an underactuated X4-AUV - Zainah, Md Zain; Wan Mohd Hafiz Shahrizan, Zaidi; Mohd Syakirin, Ramli; Hamzah, Ahmad; Mohd Shahrieel, Mohd Aras; Rozina, Abdul Rani (IEEE Xplore, 2024)
A nonlinear control method for stabilizing a X4-AUV which is underactuated system with four inputs and six degrees of freedom is presented in this research. The rotation and translation subsystems are managed using an optimal control approach combined with the backstepping method. We applied and compared two parameter tuning techniques: manual tuning and Particle Swarm Optimization (PSO). Simulation results showed that manual tuning led to smoother performance, with lower rise time, smaller steady-state error, and faster settling time than PSO-based tuning. Both methods successfully prevented overshoot, suggesting that manual tuning is more effective for this application.